Correlations between 3D mitral valve parameters and left ventricular remodeling at 6 months after ST elevation myocardial infarction: pilot study. (25th November 2020) - Scarlatescu, A.I; Onciul, S; Pascal, A; Zamfir, D; Petre, I; Onut, R; Iancovici, S; Stoian, M; Guzu, C; Vijiiac, A; Dorobantu, M
Abstract: Background: Mitral valve regurgitation and LV remodeling are associated with worse prognosis in acute ST elevation myocardial infarction (STEMI) patients. 3D echocardiography provides a more accurate assessment of mitral ring and leaflet remodeling thus offering a better understanding of mitral valve (MV) and LV geometrical changes in time. Purpose: We aimed to assess the echocardiographic evidence of the mitral valve geometrical changes after STEMI. Methods: In this prospective study we included 30 consecutive patients aged between 35 and 68 years old, with STEMI treated by primary PCI. All underwent conventional transthoracic echocardiography. In addition to conventional parameters we measured LV global longitudinal strain (GLS) and mitral valve parameters using 3D echocardiography (4D MV Assessment 2.2 software). All measuremets were performed at baseline and at 6 month follow up. LV remodeling was defined as an increase of over 15% of the LV end diastolic volume (LVEDV) at 6 months after the STEMI. Results: We found significant differences in time between LVEF (39.22% vs 43.63%, p=0.00), VTDVS (116ml vs 120ml, p=0.00), LV GLS (−13.41 vs −15.52, p=0.10). LV remodeling at 6 months after STEMI has been observed in 17% of the patients. Regarding the type of the infarction, in anterior STEMI, anterior leaflet surface increased in time (from 6.44cmp vs 7.42cmp, p=0.05), while there was no significant change in posterior leaflet area. In inferior STEMI, the area of posterior mitral leaflet decreased (4.8 cmp vs 4.5 cmp, p=0.52) as well as the leaflet length (1.42 cm vs 1.19 cm p=0.003), but the anterior leaflet remained the same. At 6 months we observed significant differences between the 2 groups (with and without LV remodeling) in the following mitral valve 3D parameters: mitral annulus area (2.6 cmp vs 1.67 cmp, p=0.02), mitral circumference (2.57 cm vs 1.74 cm, p=0.021), bicomisural diameter (2.66 cm vs 2.16 cm, p=0.018), tenting area (p=0.009), anterior leaflet length (2, 66 cm vs 2, 015 cm p=0.018) and anterior leaflet area (3, 69 cmp vs 2.49 cmp, p=0.002). Baseline LV GLS significantly correlated with the following mitral valve 3D parameters at 6 months: anterior leaflet area, posterior leaflet area, anterior leaflet length, tenting height, tenting area, mitral ring 3D area, anteroposterior and bicommissural diameters and mitral circumference (correlation coefficient >0.5). Using linear regression we proved that LV GLS can predict the shortening of the posterior MV (cut off −12.6, AUC 0.844, p=0.011) after 6 months follow up. These findings were independent of the presence and severity of mitral regurgitation. Conclusion: Using 3D echocardiography, significant changes in mitral valve geometry were detected at 6 months follow up in STEMI patients. LV remodeling is associated with increased mitral annulus dimensions. Funding Acknowledgement: Type of funding source: Other. Main funding source(s): This work was supported by CREDO Project - ID: 49182, financed through the SOP IEC -A2-0.2.2.1-2013-1 cofinanced by the ERDF.